Mitochondrial fission inhibitor Mdivi-1 alleviates lipopolysaccharide-induced parvalbumin interneurons dysregulation and cognitive impairments in a mouse model of sepsis-associated encephalopathy - Dai, Lei; Gu, Shuxin; Zhang, Yibao; Ma, Siqi; Wang, Peishan; Zhang, Jingyun; Wang, Cai; Su, Gaowei; Fu, Qun; Zhou, Wei; Fan, Yunxia (Frontiers in Pharmacology, 2025)
Introduction:Dysregulation of parvalbumin (PV) interneurons has been implicated in sepsis-associated encephalopathy (SAE), yet the underlying mechanisms remain poorly understood, and effective treatments are lacking. Given the high energy demands of PV interneurons and the emerging role of mitochondrial dynamics in SAE pathophysiology, this study aimed to investigate whether the mitochondrial fission inhibitor Mdivi-1 could alleviate PV interneuron dysfunction and cognitive impairments in a mouse model of SAE.Methods:C57BL/6 male mice were injected with lipopolysaccharide (LPS) to establish an animal model of SAE. Mdivi-1 was administered intraperitoneally 1 h before LPS challenge. Hippocampal tissues were harvested 24 h after LPS challenge for biochemical and histochemical analyses, and mitochondrial morphology was evaluated using transmission electron microscopy. In vivo electrophysiology and behavioral tests were performed between 2 and 4 days after LPS challenge to measure neural oscillations in the hippocampus and assess cognitive function.ResultsOur results showed that LPS induced neuroinflammation, mitochondrial fission abnormalities, ATP depletion, and downregulation of PV interneurons in the hippocampus, collectively contributing to reduced gamma oscillations and cognitive impairments in mice. However, these effects were mitigated by Mdivi-1 treatment.Conclusion:Our study suggests that Mdivi-1 may offer a promising therapeutic approach for attenuating PV interneurons dysfunction and cognitive impairments in SAE.